CHALLENGES IN CYBERSECURITY AND WORLDWIDE INFORMATION SECURITY - Bozorov Akmal Isroilovich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In today’s digital era, cybersecurity has become one of the most critical global issues. The rapid development of technology, widespread internet access, and increasingly  advanced  cyberattacks  have  exposed  individuals,  organizations,  and governments  to  serious  information  security  threats.  This  article  examines  major challenges in global information protection, including cybercrime, data breaches, the vulnerability  of  critical  infrastructure,  and  violations  of  personal  privacy.  It  also discusses various strategies, security frameworks, and international cooperation efforts aimed  at  reducing  cyber  risks.  The  study  highlights  that  ensuring  effective cybersecurity  and  protecting  sensitive  information  in  a  global  context  requires  a combination of technological solutions, strong policy regulations, and increased public awareness.